Parable of the talents : a graphic novel adaptation - Duffy, Damian; Butler, Octavia E. (Butler, Octavia E. Earthseed books, 2025)
"Set against a background of a war-torn continent under the control of a Christian fundamentalist fascist state, Parable of the Talents is a modern masterpiece that resonates powerfully. This graphic novel adaptation is brought to life thrillingly by Damian Duffy and John Jennings, the creative team behind the #1 New York Times bestselling adaptation of Kindred."--Publisher description.